Komunitas Hijaber dan Trend Muslim Fashion: Studi Hijaber Community Malang Jawa Timur - Setianingsih, Dwi; Thohir, Mohamad (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2024)
This article examines the phenomenon of the hijaber community in Malang, East Java. The presence of the hijaber community provides a separate space for Muslim women to express their religion in building spirituality with various forms of activities, either through religious activities or the symbols they wear, including fashion that always follows market developments. As an implementation, various types of hijaber communities for women have emerged. This article explores how the social construction built by the hijaber community in looking at the dynamics of the development of Muslim fashion trends and the dynamics that occur in the hijaber community which not only functions as a gathering place but also as a center for the development of Muslim fashion that is relevant to these religious values. By using a qualitative approach, as well as observations and interviews as a database. The findings of this study show that in addition to religious activities, the hijaber community also adapts to the development of fashion so that it is able to form a Muslim fashion trend.